2022
DOI: 10.3390/jcm11216234
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Measurements in Standing, Sitting, and Supine Position: Comparison between Tono-Pen Avia and Icare Pro Tonometers

Abstract: Background: Intraocular pressure (IOP) is influenced by body position. The purpose of this study is to compare the IOP measurements obtained with two different devices, to investigate IOP changes in standing, sitting, and supine positions. Methods: In this comparative prospective case series, IOP was measured in sitting, supine, prone, and standing (standing 1) positions and again five minutes after standing (standing 2), utilizing an Icare Pro (ICP) and a Tono-Pen Avia (TPA) in the 64 eyes of 32 healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In addition, taking into account the changes in the body position of the patients during the present study, GAT was unable to be properly managed. Furthermore, TPA has been used in similar studies where a handheld tonometer was required [ 27 ], showing comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, taking into account the changes in the body position of the patients during the present study, GAT was unable to be properly managed. Furthermore, TPA has been used in similar studies where a handheld tonometer was required [ 27 ], showing comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, obese subjects have extreme difficulty in resting their chin and forehead on the chin guard of the slit lamp to be examined. This is the reason why the study was conducted with the TPA, which uses the same physical principle as GAT to measure IOP and whose reliability is guaranteed by the numerous previous studies that have shown reliable measurements when compared to the GAT in a sitting position [ 42 , 44 ]. It should be taken in account that other external factors could cause IOP variations: for example, emotional changes could play a role, especially in subjects that are undergoing a surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty Chinese myopic children (Han nationality) who visited the First Affiliated Hospital of Zhengzhou University between June 2020 and September 2020 were recruited for this trial. In brief, aged 8-12 years, spherical equivalent refraction (SER) from −1.00D to −4.00D in both eyes, astigmatism no more than 1.50D, anisometropia of ≤1.00D, monocular best corrected visual acuity of ≥20/20 (Snellen chart), and intraocular pressures (IOPs) < 21 mmHg (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In addition, there were no other eye diseases or surgery, and no eye or systemic organic changes affecting vision acuity were enrolled.…”
Section: Methodsmentioning
confidence: 99%